Kaedah Penulisan Syeikh Daud al-Fatani Dalam Furu' al-Masa'il Dengan Tumpuan Kepada Bab Muamalat - Towpek, Hadenan (Jurnal Fiqh, 2013)
A book written in jawi, entitled Furu? al-Masa?il by Syeikh Daud al-Fatani, an Islamic religious work, is considered a masterpiece in the field of Islamic jurisprudence at the time of his appearance. The book certainly has the characteristics of greatness and certain privileges which stem from the robustness of the methods of writing. This statement leads to a question: What were the methods applied in writing this particular work? How the author structured his writing methods? Thus, this article attempts to scrutinise the writing methods applied in this book with special focus on muamalat chapter. This effort is a library research approach specifically that applies content analysis method to analyse the data. This article finds out that there are at least ten writing methods applied by the author. The author expected the findings discussed in the book will not help readers understand, digest and master knowledge in Islamic transaction, but can also be used to develop and extended dimension to the study of other disciplines in this book and his other books.